2014
DOI: 10.1089/bfm.2014.0010
|View full text |Cite
|
Sign up to set email alerts
|

Lingual Frenotomy for Breastfeeding Difficulties: A Prospective Follow-Up Study

Abstract: There are favorable long-term effects of frenotomy on breastfeeding. Lingual frenotomy does not always alleviate breastfeeding difficulties, and rarely worsening ensues. We could not find any predictor for successful breastfeeding after frenotomy. We speculate that because the procedure is minor, in the event of breastfeeding difficulties, lingual frenotomy should be considered as an effective tool to assist in long-term breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 5 publications
0
47
1
2
Order By: Relevance
“…37,43,[55][56][57][58] The panel agreed that informed consent for lingual frenotomy should include mention of the possibility of failure to experience improvement in breastfeeding ( Table 4). While much evidence in the literature supports the idea that lingual frenotomy can lead to improvement in breastfeeding, 43,44,46,50,51,54,[59][60][61][62][63][64][65][66][67][68][69][70][71][72] it is also important to recognize that not all infant-mother dyads experience breastfeeding improvement after the procedure. 5,45,51,62 The panel also reached consensus that patients and caregivers of patients with ankyloglossia should be counseled about nonsurgical options, including observation, lactation consultation, and/or speech-language pathology consultation ( Table 4).…”
Section: Frenotomy Indications and Informed Consentmentioning
confidence: 99%
“…37,43,[55][56][57][58] The panel agreed that informed consent for lingual frenotomy should include mention of the possibility of failure to experience improvement in breastfeeding ( Table 4). While much evidence in the literature supports the idea that lingual frenotomy can lead to improvement in breastfeeding, 43,44,46,50,51,54,[59][60][61][62][63][64][65][66][67][68][69][70][71][72] it is also important to recognize that not all infant-mother dyads experience breastfeeding improvement after the procedure. 5,45,51,62 The panel also reached consensus that patients and caregivers of patients with ankyloglossia should be counseled about nonsurgical options, including observation, lactation consultation, and/or speech-language pathology consultation ( Table 4).…”
Section: Frenotomy Indications and Informed Consentmentioning
confidence: 99%
“…Among studies reporting harms, bleeding was most frequently reported. 8,16,19,33,37 Bleeding was typically described as minor and limited, and would be expected with a minor surgical intervention. Few studies described what specific methods were used to collect harms data.…”
Section: Harmsmentioning
confidence: 99%
“…Forty-six studies reported that they looked for harms; either reporting actual harms or reporting that they found none. These included 5 RCTs, 7-11 1 cohort study, 12 25 case series, 13,15,16,[18][19][20][21][24][25][26][27][28][29][30]32,33,[35][36][37][38][39][40][41][42][43] and 15 case reports. [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Most studies reporting harms information explicitly noted that no significant harms were observed (n = 17) 7,[9][10][11]13,15,18,20,24,…”
mentioning
confidence: 99%
“…Argiris et al, Srinivasan et al and Hogan et al reported 89% breastfeeding at 6 week follow-up, 77.8% at 3 months and 60% at 4 months respectively [5,18,23]. Berry et al described rates of 65% at 3 months and 51% at 4.5 months [14] and Dollberg et al reported continued breastfeeding in 89% at 2 weeks, 68% at 3 months and 56% at 6 months [31]. When comparing these rates with the national rates it is important to consider that the studies are likely to select for motivated individuals however the sizeable difference between the rates strongly suggests a positive influence with frenotomy.…”
Section: Effect On Breastfeedingmentioning
confidence: 96%